Earthworm Extract (Pheretima javanica K) Against Typhus Disease: Literature Review - Lestari, Mugi; Ibrahim, Riza A (International Journal of Health, Medicine, and Sports, 2024)
This literature review examines the potential use of earthworm extract (Pheretima javanica K) as an alternative treatment for typhus disease. The study analyzes multiple research findings regarding the antibacterial properties of earthworm extracts against Salmonella typhi, the causative agent of typhus. Through a comprehensive review of studies from Web of Science, PubMed, and Google Scholar databases, this research evaluates the effectiveness of different earthworm species and extraction methods. The findings indicate that Pheretima javanica shows promising antimicrobial properties, particularly when extracted with ethanol, while other species such as Lumbricus rubellus demonstrate limited effectiveness. Pheretima javanica shows promise, other species like Lumbricus rubellus demonstrate limited or no significant antibacterial activity against Salmonella typhi. The success of treatment appears to be heavily dependent on factors such as extraction technique, concentration, and testing methodology. Animal studies, particularly those using white rats, have shown encouraging results with specific dosages, but human trials remain necessary to establish clinical efficacy and safety. The varying results across different studies emphasize the need for standardized extraction methods and testing protocols to ensure consistent outcomes.